Fragility analysis of a containment structure under far-fault and near-fault seismic sequences considering post-mainshock damage states. (1st November 2019) - Bao, Xu; Zhang, Mao-Hua; Zhai, Chang-Hai
Highlights: The effect of fault types of aftershocks on a damaged containment is investigated. The floor acceleration amplification for post-mainshock structures is identified. Seismic demands on secondary systems are studied through floor response spectrum. Fragility analysis under different fault types of seismic sequences is performed. The influence of post-mainshock damage states are considered. Abstract: Due to the unique characteristics of near-fault ground motions with an intense pulse, near-fault seismic sequences have the potential to cause more severe damage to structures compared to far-fault seismic sequences. This study focuses on quantitatively comparing the seismic response and fragility of a containment structure subjected to near-fault and far-fault seismic sequences. For this purpose, both as-recorded and artificial seismic sequences are used as input to conduct the nonlinear dynamic analysis. The effect of fault types of aftershocks on a mainshock-damaged containment is investigated in terms of the global response and local damage, respectively. Seismic demands on secondary systems are also studied through floor response spectra considering post-mainshock damage states. To evaluate the influence of near-fault and far-fault seismic sequences on the fragility of a containment structure, a new methodology is used to generate fragility curves, which can effectively consider the effect of post-mainshock damage states when computing the exceedance probability. The results show that near-fault seismic sequences can cause greater dynamic responses of a containment than far-fault ground motions, and the fragility evaluation without considering near-fault seismic records can overestimate the safety margin of a containment structure.